Recording Students’ Performance in Physical Education Using Mobile-Based Applications - Kurniawan, Wahyu Ragil; Setiawan, Ipang; Rozi, Fatkhur; Rahman, Alvin Yanuar; Shidiq, Abdul Aziz Purnomo (Department of Physical Education, Sport, Health and Recreation, 2021)
The aim of this study is to analyze products based on mobile application development in helping teachers record student performance in physical education. Development method was carried out by the following procedure: requirement analysis; initial product development; expert validation; field trials; product revision; and final result. Interview guides, validation sheets, and questionnaire sheets were distributed in data collection process. Expert validation result on the phase I obtained average 76% which is classified as good criteria, and on the phase II obtained average 81,33% which is classified as very good criteria. While on the small scale trial obtained average 69,88% which is classified as good criteria, and on the big scale trial obtained average 79,40% which is classified as good criteria. Conclusion of the study shows that the mobile application product can be used to assist teachers in recording student performance in Physical Education which can be accessed by teachers, students, and parents of students.